Nighttime magnetic field fluctuations in the topside ionosphere at midlatitudes and their relation to medium‐scale traveling ionospheric disturbances: The spatial structure and scale sizes. Issue 8 (12th August 2015) - Park, Jaeheung; Lühr, Hermann; Kervalishvili, Guram; Rauberg, Jan; Michaelis, Ingo; Stolle, Claudia; Kwak, Young‐Sil
Abstract Previous studies suggested that electric and/or magnetic field fluctuations observed in the nighttime topside ionosphere at midlatitudes generally originate from quiet time nocturnal medium‐scale traveling ionospheric disturbances (MSTIDs). However, decisive evidences for the connection between the two have been missing. In this study we make use of the multispacecraft observations of midlatitude magnetic fluctuations (MMFs) in the nighttime topside ionosphere by the Swarm constellation. The analysis results show that the area hosting MMFs is elongated in the NW‐SE (NE‐SW) direction in the Northern (Southern) Hemisphere. The elongation direction and the magnetic field polarization support that the area hosting MMFs is nearly field aligned. All these properties of MMFs suggest that they have close relationship with MSTIDs. Expectation values of root‐mean‐square field‐aligned currents associated with MMFs are up to about 4 nA/m2. MMF coherency significantly drops for longitudinal distances of ≥1∘.